2008
DOI: 10.1021/ma702267e
|View full text |Cite
|
Sign up to set email alerts
|

Branching and Higher Order Structure in Banded Polyethylene Spherulites

Abstract: Because of twisting correlation of crystallites along the radial direction, polyethylene spherulites are known to develop concentric band pattern. The mechanism of branching and reorientation of lamellar crystallites in the banded spherulites has been examined experimentally by optical and atomic force microscopies associated with quenching and chemical etching. The microscopic observation suggests a branching instability of lamellar crystals at the growth front of the spherulite. We propose a mechanism of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 72 publications
10
99
1
4
Order By: Relevance
“…In our previous papers, we have reported successful confirmation of the predicted square root dependence of m on VD À1 (or V) in terms of the temperature dependence for polyethylene 16 and polybutene-1, 17 irrespective of the higher order structures of banded and non-banded spherulites. For the banded spherulites of polyethylene, the proportional relationship between P and m in eq 1 has also been confirmed.…”
Section: 2mentioning
confidence: 54%
See 2 more Smart Citations
“…In our previous papers, we have reported successful confirmation of the predicted square root dependence of m on VD À1 (or V) in terms of the temperature dependence for polyethylene 16 and polybutene-1, 17 irrespective of the higher order structures of banded and non-banded spherulites. For the banded spherulites of polyethylene, the proportional relationship between P and m in eq 1 has also been confirmed.…”
Section: 2mentioning
confidence: 54%
“…[18][19][20] We have recently suggested a splaying instability due to a gradient field of free energy at the growth front and experimentally confirmed the predicted dependence for the case of banded polyethylene spherulites and non-banded polybutene-1 spherulites. 16,17 As the splaying instability of growth front, we have suggested two possibilities of the gradient in free energy at the growth front formed by (1) compositional gradient of non-crystallizing fractions (MullinsSekerka's type 21,22 ) and by (2) pressure gradient due to the difference in densities of the crystal and the melt (SaffmanTaylor's type 23,24 ). The gradient in free energy accelerates the fluctuation of the growth front and the surface tension suppresses the fluctuation; the balance of those two effects determines the critical lateral width, m .…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to poor cooperative packing of twisting lamellae and probably results in the irregular banded structure at high temperatures. Toda et al [50][51][52] have systematically revealed the role of macro screw dislocations in lamellar branching in the banded polymer spherulites.…”
Section: Organization Of Twisted Lamellae In Banded Spherulitesmentioning
confidence: 99%
“…[99,165,167,267,[274][275][276] Allgemein ist noch keine Theorie der Organisation verwundener Lamellen in Sphärolithen verfügbar. Aus Beobachtungen an Poly(l-milchsäure), [120] Poly(ethylen), [124,125] Poly(R-3-hydroxybutyrat) [148] und Poly(vinylidenfluorid) [166] sowie aus unseren eigenen Beobachtungen an Mannit und Tetraphenylblei (Abbildung 1 f) ist bekannt, dass gut organisierte gebänderte Muster nur bei kleinen Verwindungsperioden entstehen. Starke Verwindung scheint alle anderen Inhomogenitäten zu unterdrücken.…”
Section: Morphologie Von Individuenunclassified